Faglegheit i litteraturundervisninga? Nokre litteraturlærarmodellar til diskusjon - Kjelen, Hallvard (Nordlit, 2022)
This article is a contribution to the debate on the legitimation and status of literature teaching in the prevailing educational and professional policy context . In the introduction, the article presents some of the most important challenges for literature teaching in schools: one approach to teaching literature that is too poorly anchored, and another one that has a professional foundation, but still do not manage to extract the full potential of literature teaching. The article finally presents some literature didactic positions that can point to possible solutions.